Look What I Found! Augmenting Phone Calls with Memories of the Past - Gouveia, Élton; Azevedo, Francisco; Ferreira, Luís; Caldeira, Paulo; Almeida, Vítor; Gouveia, Rúben; Karapanos, Evangelos (My University, 2013)
Photos have an enormous capacity in cueing memories of our past and supporting collective reminiscing. Yet, despite the considerable increase in our ability to efficiently capture photos, our digital photo collections remain to a large extent invisible to our everyday interactions with the physical world. We present the design of “Look what I found!”, a mobile application that aims at supporting collective reminiscing through making photos present in our daily phone calls. We then report the field trial of “Look what I found!” that discovered unexpected and often inventive ways in which users appropriate the application in their daily lives.
Keywords: Experiences; Nostalgia; Photos; Serendipity; Sharing